Pengaruh Kompensasi, Kepemimpinan dan Komitmen Organisasi terhadap Kinerja Manajerial pada SKPD Kota Lhokseumawe - Marbawi Adamy (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
The purpose of this research have to test the influence of compensation, leadership, and organization commitment on the managerial performance in SKPD Kota Lhokseumawe. Hypotheses that proposed is budgetary participation, leadership, and organization commitment to the managerial performance is significant with simultaneous test or partial test in SKPD Kota Lhokseumawe The population of this research is leader and financial staff in office of SKPD usually in making budgetary policy amount 65 persons (source data in employer unit, 2009). The adjustment small population also this research with census. And than process and analyze data by using multiple regression models through SPSS version 14. The result of this research is in the simultaneous compensation, leadership, and organizational commitment significantly influence on managerial performance, and with partial test budgetary participation, leadership, and organizational commitment is positively significant influence on managerial performance in SKPD Kota Lhokseumawe.Keywords: compensation, leadership, organization commitment, managerial performance